(untitled) (CIPEEX, 2025)
Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic has caused an unprecedented global health crisis, requiring rapid and efficient responses from health systems. In this context, clinical analysis laboratories have become fundamental in both the etiological diagnosis and the monitoring and prognosis of the disease. Objective: To address the main advances in clinical analysis driven by the COVID-19 pandemic. Methodology: This was a narrative review based on scientific and institutional sources published between 2020 and 2025. The search was conducted in SciELO, PubMed, and Google Scholar, using the descriptors "COVID19," "analysis," "laboratory," and "clinical," combined by Boolean operators AND and OR. Articles published between 2020 and 2025, in Portuguese or English, with free access, were included. Duplicate works unrelated to the topic were excluded. Results: Among the most relevant methods, the Polymerase Chain Reaction with Reverse Transcriptase stood out, considered the gold standard due to its high sensitivity and specificity. The incorporation of point-of- care devices, automated platforms, artificial intelligence, and adaptive algorithms also optimized the collection, analysis, and interpretation of laboratory data. Laboratories also faced challenges in the pre- analytical phase, such as structural adaptation, biosafety control, and validation of new reagents. In addition, the growing use of technologies such as microfluidics and real-time analysis contributed to faster and more reliable responses. Conclusion: The methodological advances adopted during the pandemic not only expanded the diagnostic capacity of laboratories, but also established a solid foundation for addressing future public health emergencies, consolidating a new era for clinical analysis.